ANALISIS PERBANDINGAN KINERJA ANTARA PERBANKAN SWASTA NASIONAL DEVISA DAN PERBANKAN BUMN - wartini, putu sri; wirakusuma, gede made (E-Jurnal Akuntansi, 2015)
Banking institutions can be divided into state-owned banks and state-owned private banks foreign exchange private property. Classification of banks could cause the difference in the performance of each of the banks concerned. Good performance will encourage investors to invest in the bank concerned. This study used a sample of Statedon banks 4 and 19 private banks listed in Indonesia Stock Exchange in 2009-2013. Sampling method used is purposive sampling..Hasil in this study third-party funds significant negative effect on the performance of banks, loan-to-deposit ratio is significant ed negative effect on the performance and debt to equity ratio is significant negative effect s on bank performance. Based the results of previous studies are average difference between the performance of state-owned banks with private banking, while the results in this study there was no difference between SOEs and private banking banking foreign national.
Keywords: banking performance, third-party funds, loan to depposit ratio, debt to equityratio